Achilles tendon loading is lower in older adults than young adults across a broad range of walking speeds - Ebrahimi, Anahid; Loegering, Isaac F.; Martin, Jack A.; Pomeroy, Robin L.; Roth, Joshua D.; Thelen, Darryl G. (Experimental gerontology, 2020)
The purpose of this study was to investigate age-related differences in Achilles tendon loading during gait. Fourteen young (7F/7M, 26 ± 5 years) and older (7F/7M, 67 ± 5 years) adults without current neurological or orthopaedic impairment participated. Shear wave tensiometry was used to measure tendon stress by tracking Achilles tendon wave speed. The wave speed-stress relationship was calibrated using simultaneously collected tensiometer and force plate measures during a standing sway task. Tendon stress was computed from the force plate measures using subject-specific ultrasound measures of tendon moment arm and cross-sectional area. All subjects exhibited a highly linear relationship between wave speed squared and tendon stress (mean R2 > 0.9), with no significant age-group differences in tensiometer calibration parameters. Tendon wave speed was monitored during treadmill walking at four speeds (0.75, 1.00, 1.25, and 1.50 m/s) and used to compute the stress experienced by the tendon. Relative to young adults, older adults exhibited 22% lower peak tendon wave speeds. Peak tendon stress during push-off in older adults (24.8 MPa) was 32% less than that in the young adults (36.7 MPa) (p = 0.01). There was a moderate increase (+11%) in peak tendon stress across both groups when increasing speed from 0.75 to 1.50 m/s (main effect of speed, p = 0.01). Peak tendon loading during late swing did not differ between age groups (mean 3.8 MPa in young and 4.2 MPa in older adults). These age-related alterations in tendon tissue loading may affect the mechanobiological stimuli underlying tissue remodeling and thereby alter the propensity for tendon injury and disease. •Shear wave sensors can measure superficial tendon stress noninvasively.•Achilles tendon stress is 32% lower in older than younger adults during walking.•Achilles tendon loading is lower in older adults across a range of walking speeds.•Diminished loads could alter mechanobiological stimuli underlying tendon remodeling.